Pengaruh Pemanfaatan Teknologi Informasi Akuntansi, Kompetensi SDM, dan Pengendalian Internal Terhadap Kualitas Laporan Keuangan Pemerintah Daerah Pada OPD Kabupaten Kebumen - Amanda Yulia Damayanti; Chaidir Iswanaji; Siti Arifah (Journal of Creative Student Research, 2024)
There are several factors that affect the quality of local government financial reports, namely the utilization of accounting information technology, HR competencies, and internal control. This study aims to determine the effect of utilization of accounting information technology, HR competencies, and internal control on the quality of local government financial reports at OPD Kebumen Regency. This study used 21 OPD samples in Kebumen Regency using purposive sampling. This research method is a quantitative method using multiple linear regression analysis. Based on the results of the research that has been done, it can be concluded that the use of accounting information technology has a negative and insignificant effect on the quality of LKPD, human resource competence has a positive and significant effect on the quality of LKPD, and internal control has a positive effect on the quality of LKPD. It is hoped that the OPD of Kebumen Regency can maintain and improve HR competence and internal control and it is hoped that the utilization of accounting information technology is used as much as possible in order to produce quality local government financial reports.